An Essential Role for (p)ppGpp in the Integration of Stress Tolerance, Peptide Signaling, and Competence Development in Streptococcus mutans - Kaspar, Justin; Kim, Jeong N.; Ahn, Sang-Joon; Burne, Robert A. (Frontiers in Microbiology, 2016)
The microbes that inhabit the human oral cavity are subjected to constant fluctuations in their environment. To overcome these challenges and gain a competitive advantage, oral streptococci employ numerous adaptive strategies, many of which appear to be intertwined with the development of genetic competence. Here, we demonstrate that the regulatory circuits that control development of competence in Streptococcus mutans, a primary etiological agent of human dental caries, are integrated with key stress tolerance pathways by the molecular alarmone (p)ppGpp. We first observed that the growth of a strain that does not produce (p)ppGpp (ΔrelAPQ, (p)ppGpp0) is not sensitive to growth inhibition by comX inducing peptide (XIP), unlike the wild-type strain UA159, even though XIP-dependent activation of the alternative sigma factor comX by the ComRS pathway is not impaired in the (p)ppGpp0 strain. Overexpression of a (p)ppGpp synthase gene (relP) in the (p)ppGpp0 mutant restored growth inhibition by XIP. We also demonstrate that exposure to micromolar concentrations of XIP elicited changes in (p)ppGpp accumulation in UA159. Loss of the RelA/SpoT homolog (RSH) enzyme, RelA, lead to higher basal levels of (p)ppGpp accumulation, but to decreased sensitivity to XIP and to decreases in comR promoter activity and ComX protein levels. By introducing single amino acid substitutions into the RelA enzyme, the hydrolase activity of the enzyme was shown to be crucial for full com gene induction and transformation by XIP. Finally, loss of relA resulted in phenotypic changes to ΔrcrR mutants, highlighted by restoration of transformation and ComX protein production in the otherwise non-transformable ΔrcrR-NP mutant. Thus, RelA activity and its influence on (p)pGpp pools appears to modulate competence signaling and development through RcrRPQ and the peptide effectors encoded within rcrQ. Collectively, this study provides new insights into the molecular mechanisms that integrate intercellular communication with the physiological status of the cells and the regulation of key virulence-related phenotypes in S. mutans.